Impact of Florida Medicaid guidelines on frequency and cost of delayed circumcision at Nemours Children's hospital. Issue 6 (December 2022) - Soto, Susana; Hernandez, Kailee; Colon-Sanchez, Kaity; Ellsworth, Pamela
Summary: Introduction: In 2003, Florida Medicaid discontinued coverage of routine neonatal circumcision (NC) resulting in an increase in nonneonatal circumcisions. Florida Medicaid is one of 16 state healthcare plans that do not cover NC. Florida Medicaid covers male circumcision in a child ≥3 years for a defined medical indication or persistent phimosis refractory to topical steroid therapy (TST). We sought to assess the economic impact of the evaluation and management of phimosis/circumcision in Florida Medicaid males ≥3 years treated at Nemours Children's Hospital. Study design: We performed an IRB approved retrospective chart review of all male Florida Medicaid patients ≥3 years seen at NCH for phimosis/circumcision from Sept. 2016–Sept. 2019. Data extracted included demographics, age at presentation, prior treatment with TST, response to TST, and surgical interventions. The patients were stratified into three management groups. Total costs for each group were based upon estimated Medicaid reimbursement rates. Data were analyzed using descriptive analysis on SPSS. Results: Seven hundred and sixty-three males were evaluated. Age at presentation ranged from 3 to 17 years and 59% of patients were 3–6 years at initial presentation. Three hundred and forty patients underwent circumcision. The total estimated cost of care for all patients was $1, 345, 533.90. This compares to an estimated cost of $171, 675 if all individuals underwent NC at 2020 costs. Conclusions: The total estimated cost associated with the evaluation and management of 763 patients ≥3 years for phimosis/circumcision was 7.8 times the estimated cost of NC for all these patients and likely is an underestimation of the true difference in cost as we did not account for additional visits outside of the initial consultation and follow-up, post-operative visits outside of the global period, emergency room visits, and returns to operating room. Of the circumcisions performed, only 18.5% met Florida Medicaid defined medical indications. Success rates for TST range from 53.8 to 95% in the literature, however, our success rate was 34.3%. The reason for the variation in response rate between our results and the literature may reflect that caretakers desiring circumcision may be less compliant with TST use. Only 6.6% of patients had a documented failure of TST prior to initial presentation. Further education of PCPs on current Medicaid/MCG guidelines for the evaluation and management of phimosis, as well as PCP adoption of TST, could reduce the number of unnecessary office visits, healthcare costs, and family burden.